Spatial proximity between polyploids across South American frog genera - David, Kyle T.; Halanych, Kenneth M. (Journal of biogeography, 2021)
Aim Polyploids have been theorized to occur more frequently in environments that are subjected to severe conditions or sudden disruptions. Here we test the expectation that polyploid taxa occur more frequently in extreme or disrupted environments than their diploid counterparts, whether due to increased adaptive potential, environmental resilience or cross‐ploidy competition. Location South America. Taxon All frog genera in the area with both polyploid and diploid member species (Ceratophrys, Chiasmocleis, Odontophrynus, Phyllomedusa and Pleurodema). Methods In all, 13,556 occurrence records of 82 frog species were collected from the Global Biodiversity Information Facility. Species distribution models, range overlap estimates, statistical tests and principal component analyses were used to estimate and compare environments between diploid and polyploid species within and across genera using several categorical and quantitative variables taken from multiple publicly available sources. Results Almost all polyploid occurrences are found within southeastern South America, largely to the exclusion of diploids. Polyploid species occur more closely with intergeneric polyploids than they do with congeneric diploids. Southeastern South America is more temperate, seasonal and less forested when compared to the tropical environments more commonly inhabited by diploids. The habitat ranges of polyploid species are subject to greater temperature fluctuations than diploid species. This region has also experienced major transformations in the modern era, owing to an agriculture boom over the last century. Polyploid occurrences are more likely to be found in areas with greater cropland usage, fertilizer application and pesticide application than diploids. Main Conclusions Across species, temperature seasonality was the only variable with strong statistical differences between diploids and polyploids. Greater annual fluctuations in temperature may lead to more established polyploid species due to reasons mentioned above; however, extreme temperature differences are also known to contribute to polyploid gamete formation, providing a possible non‐selective explanation. Polyploid occurrences are also more likely to be found in areas of high agricultural impact, providing support for the hypothesis that polyploids are more resilient to environmental disruptions than diploids.